Consumer Preferences on Purchase of Residential Home in Cimahi Region: Application of Factor Analysis - Ibrahim, Shiddiq (Journal of Innovation, Business and Entrepreneurship, 2019)
Abstract. The increase of population growth rate will also lead it into an increase of houses needs. One of primary human needs is needs of residence. As a place to live in, residential is one of primary needs other than food and clothing needs. So this research would like to know that the consumer preferences on purchase of residential home in Cimahi region, application by factor analysis. The problem is that there are still limited basic guideline on creating marketing strategy that based on the consumer preferences when browsing to look for the residential home they needed. By making an efficient and effective marketing strategy based on the consumer needs of residential home to keep the consumer engagement similar with the company’s product is one of the things that wanted to be solved. By not knowing what important features of the residential home to be delivered will be ended up in decrease of consumer expectation, which will have an impact on the company's image and trust. The method of this research is quantitative and use the application of factors analysis, namely research methods based on the philosophy of positivism, used to examine certain populations or samples, data collection method used in this study is descriptive analysis, with the aim to find the most dominant factor that influence consumer on purchase of residential home in Cimahi region. The results shows that the dominant factor that drives consumers to purchase residential homes is the factor of affordable houses with good material quality that can explain the drivers of purchasing residential homes. Based on the conclusions from the results of the study, the suggestions for this research, referring to the dominant factor that drives consumers to purchase residential homes is affordable houses with good material quality, that could be done by give more attention to four aspects: Proper land acquisition, construction speed, selection for the concept of a residential home, and determination of selling prices. These indicators can be used in promotional and marketing activities, because respondents have a positive perception of affordable houses with good material quality. Therefore the promotion that will be carried out must show the quality of the product and emphasis on affordable prices. The implementation process from this research must be conducted by the company itself based on the value of the company.Keywords: Purchase intention, Residential home, Consumer preferences, Purchasing decision making process.